2022
DOI: 10.51983/ajsat-2022.11.1.3204
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Universal Human Values for Life: A Study

Abstract: The human values are beliefs that have a deep-rooted worth in usefulness or importance to the holder of these qualities. These values are necessity in today’s society and education system. These values provide a meaning to the life of a human being. Usually, people become lazy and dull after being successful in this materialistic world, but if they have values, they would always have a purpose and guide in their life. Values are needed to teach to the children from the early age at school. This will help them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Building a strong teacher-student relationship can be more challenging in a virtual setting. The absence of face-to-face interactions can hinder the development of rapport and the ability to provide personalized guidance [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. 7.…”
Section: Merits and Demerits Of Computer Assisted Educationmentioning
confidence: 99%
“…Building a strong teacher-student relationship can be more challenging in a virtual setting. The absence of face-to-face interactions can hinder the development of rapport and the ability to provide personalized guidance [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. 7.…”
Section: Merits and Demerits Of Computer Assisted Educationmentioning
confidence: 99%
“…Numerous studies have emphasized the importance of life values over the years. According to Rani et al (2022), values give meaning to the life of human beings and the education system must instill them in children from a young age. Schwartz (1992) suggested that basic values act as guiding principles that explain how people and communities make decisions and behave in certain ways.…”
Section: Importance Of Lifementioning
confidence: 99%